(untitled) (Global Journal of Human-Social Science, 2022)
There was no particular problem to come up with a topic for an article on the work of Carlos Reagados since it was the Light that was issued by the author in the title of the film The problem arose later The internal understanding of the film which absolutely responded resonated with this name suddenly turned out to be torn the concept as it were bifurcated parted to two rather autonomous parts And although in principle these components did not contradict each other the cleanliness of the work demanded to determine the new position Oddly enough the reason for the schism was an event that although at first glance was not directly related to Reagados and in general to cinema this reason became the epidemic of coronovirus literally falling on our heads What an amazing paradox and what an evil irony is - what is the same We received the crown which immediately discovered the fullness of the bitter truth - the king is naked All of us or almost all by default believing ourselves kings of nature were in complete unpreparedness and confusion before meeting with this very nature which without a special announcement gave us the long -awaited crown In an instant science revealed its helplessness and inefficiency encountering With the phenomenon of the coronovirus which literally turned the world Croovirus brightly demonstrated that the old idea that is going to the era of education that a person is omnipotent and capable of abbreviated and control the world is an illusion And the illusion is dangerous Today we reap the fruits of our rampant and victorious activity And only serious failures suddenly give rise to the question are we acting correctly And how does the world respond to our sometimes shameless intervention and irresponsible attempts to finally adapt this world to its needs Coronovirus contains a tough message - we moved to a dangerous line and we must radially change our vision of the world and the attitude towards it But no changes will happen until a person realizes that first of all he needs to remember himself his own properties And it was in the context of this in the full sense of the word of the world event the films of Reagados began to play with a new meaning which allowed to more accurately identify the core of his special philosophy and directorial discourse which we define the picture of the world which we define as the single world and which however further enhances The semantic significance of the category Light as a structural -forming mechanism of the film Thus the task was complicated by the need to enter into consideration at once two concepts of concepts - light and single world